THE EFFECT OF PERSONALITY TRAITS ON LEADERSHIP BEHAVIORS: A RESEARCH ON THE STUDENTS OF BUSINESS ADMINISTRATION DEPARTMENT - Agah Sinan Ünsar; Serol Karalar (Economic Review)
In leadership definitions, it is generally approved that superior personality traits are one of the factors which form successful leadership. Furthermore, individuals follow leaders consistently and choose leaders as their role models. In this context; the purpose of this study is to investigate the effect of personality traits on leadership behaviors. Thus; a questionnaire has been implemented on the students of Trakya University Faculty of Economic and Administrative Sciences (FEAS) and Vocational School of Social Sciences, Departments of Business Administration (Edirne-Turkey). Subsequently the findings have been commented by means of analyses and tables. Gender, grow-up places, educational level of students’ parents and types of high schools which students graduated from were found to affect the adopted leadership styles. Besides that, there are differences between the FEAS and the Vocational School students on extravert, responsible, open to experience personality traits and laissez-faire leadership style.